Stabilization treatment of cultural heritage artefacts: In situ monitoring of marine iron objects dechlorinated in alkali solution. (March 2018) - Kergourlay, F.; Réguer, S.; Neff, D.; Foy, E.; Picca, F.-E.; Saheb, M.; Hustache, S.; Mirambet, F.; Dillmann, P.
Highlights: β-Fe2 (OH)3 Cl dissolve within few minutes when immersed in NaOH. Fe(OH)2 and Fe3 O4 form both in NaOH aerated and deaerated. Chlorinated green rust forms during the dechorination in aerated solution. Unwashed corrosion layers contain chlorine after drying. Deaerated solution conduct to a more homogeneous layer mainly constituted of goethite. Abstract: The preservation of archaeological iron artefacts necessitates stabilization treatments. For this study, such treatments were applied, in aerated and deaerated NaOH solutions, to Roman iron bars excavated from a marine site in order to understand the evolution of corrosion layers composed of ferrous hydroxychloride β-Fe2 (OH)3 Cl. Their transformation was monitored in situ by micro-diffraction under synchrotron radiation and characterized ex situ using multi-scale complementary analytical tools. The formation of transient phases such as ferrous hydroxide Fe(OH)2 was identified in both media and chlorinated green rust GR(Cl − ) occurred in aerated solutions, showing the influence of dissolved oxygen on the transformation processes.